How Militaries Learn : human capital, military education, and battlefield effectiveness - Toronto, Nathan W., author (Lanham, Maryland: Lexington Books, 2018)
"Modern weapons and plentiful resources matter little if militaries cannot organize efficiently, exercise initiative, and take advantage of opportunities as they arise."
Keywords: Strategic Culture; Military Art and Science; Military Education; Organizational Change; Armed Forces -- Officers